Pengaruh Faktor Pribadi Terhadap Keputusan Konsumen Pengiriman Paket Pada PT. Pos Indonesia (PERSERO) Jambi - Puja Rahayu (Universitas Batanghari Jambi, 2019)
The purpose of this study was to determine the existence of personal influences in consumer decisions in package delivery at PT. Pos Indonesia (Persero) Jambi. The method used is the survey method using Primary and Secondary, the method of data collection is taken from library research and field research with a population that includes all consumers who use package delivery at PT.Pos Indonesia (Persero) Jambi and use 100 research samples. The analytical method in this study is descriptive with the analysis tool using simple linear equations, test the coefficient of determination, and hypothesis testing. From simple linear results Y = 1.717 + 0.479X there is a positive influence between the relationship of personal factor variables and consumer decisions.